Music, labor, and capitalism in Manila's transforming colonial society in the late nineteenth century - Tan, Arwin Quiñones
"This dissertation examines the relation of music and capitalism in Manila which was constitutive of the critical period of modernity in the late nineteenth and early twentieth centuries (1878-1913). Capitalism pushed for a culture ruled by the consumption of commodities in the market, introduced new forms of exchanges---particularly of money---and transformed the mode of production of music in the public sphere. The new economic system provided a good base for the globalizing and modernizing projects of the two successive colonial masters---Spain and the USA. It activated changes in social relationships that altered music making in the colony with new material and social practices such as the market-driven valuation of musicians' labor; the development of music literacy; the institutionalization of secular-based music academic and performing groups; the creation of strategies for more opportunities and social representation through forming musical associaions; the crucial contribution of paternalistic patron-client relations, even inviting the participation of women in music productions; the increased commodification of music expressions; and the domestic consumption of printed popular music. A central institution of this economic system was the market--the paying public comprised of the established colonial elite and the growing Filipino middle class who used their developed taste for Western music as a marker for their social status and the production of this as cultural capital.